Qualidade da madeira de clones de eucalipto utilizados na produção de celulose - Carneiro, Marcia Fernanda (2017)
Grown in large scale in Brazil, the genus Eucalyptus is stands out in the national economy and is the main source of feedstock to pulp and paper industry. Because it is a complex and heterogeneous material, the set of wood properties vary from genus, species, individual and cell. Some indicators are common to define the quality of the wood, for example, the specific gravity. But, it is important that the anatomical properties are studied in order to make an accurate diagnosis regarding the final use of the wood. The general objective of this research was to evaluate the physical and anatomical properties of the wood of clones the Eucalyptus grandis x Eucalyptus urophylla for the production of cellulose. 12 clones were evaluated at 6 years old from clonal plantations located in Aracruz, state of Espírito Santo, Brazil, coming to the company Fibria Celulose S.A. Total of five trees were evaluated per clone, totalized sixty trees evaluated at the end. The results indicated variations in specific gravity along the trunk in the base-top direction and variations of the clones. In clones two and nine a variation of the mean specific gravity of 0.47 g cm-3 at 0.59 g cm-3 , respectively, was observed. In the pit-bark direction, the specific gravity had low values in the first centimeters of the radius and increased towards the periphery. The clone six presented the highest mean propagation velocity of the tension wave in the longitudinal direction of the trunk, in the DBH region and had a statistical difference. In the anatomy of the wood, variations in the quantitative and qualitative of the wood of the different genetic materials were observed. Correlations were high and significant between total height and DBH; Specific gravity and cell wall thickness of the fibers; Fire diameter and vascular frequency; and MFA and cell wall thickness of the fibers.